Targeting mitochondrial dysfunction in amyotrophic lateral sclerosis: a systematic review and meta-analysis. Issue 1 (6th August 2019) - Mehta, Arpan R; Walters, Rachel; Waldron, Fergal M; Pal, Suvankar; Selvaraj, Bhuvaneish T; Macleod, Malcolm R; Hardingham, Giles E; Chandran, Siddharthan; Gregory, Jenna M
Abstract: Interventions targeting mitochondrial dysfunction have the potential to extend survival in preclinical models of amyotrophic lateral sclerosis. The aim of this systematic review was to assess the efficacy of targeting mitochondria as a potential therapeutic target in amyotrophic lateral sclerosis. Preclinical studies written in the English language were identified with no restrictions on publication date from PubMed, Medline and EMBASE databases. All studies adopting interventions targeting mitochondria to treat amyotrophic lateral sclerosis in genetic or drug-induced organism models were considered for inclusion. A total of 76 studies were included in the analysis. Survival data were extracted, and the meta-analysis was completed in RevMan 5 software. We show that targeting mitochondrial dysfunction in amyotrophic lateral sclerosis results in a statistically significant improvement in survival ( Z  =   5.31; P  <   0.00001). The timing of administration of the intervention appears to affect the improvement in survival, with the greatest benefit occurring for interventions given prior to disease onset. Interventions at other time points were not significant, although this is likely to be secondary to a lack of publications examining these timepoints. The quality score had no impact on efficacy, and publication bias revealed an overestimation of the effect size, owing to one outlier study; excluding this led to the recalculated effect size changing from 5.31 to 3.31 ( P  <   0.00001). The extant preclinical literature indicates that targeting mitochondrial dysfunction may prolong survival in amyotrophic lateral sclerosis, particularly if the intervention is administered early. A limitation of current research is a significant bias towards models based on superoxide dismutase 1, with uncertainty about generalisability to amyotrophic lateral sclerosis with an underlying TAR DNA binding protein 43 proteinopathy. However, further mechanistic research is clearly warranted in this field. Abstract : Here, we show a systematic review and meta-analysis of preclinical studies modelling amyotrophic lateral sclerosis and, specifically, examining mitochondrial dysfunction as a putative therapeutic target. Seventy-six studies were included, revealing that there is likely to be translational potential in targeting mitochondrial dysfunction, particularly if the intervention is delivered early. Graphical Abstract: